Application of Symmetric Encryption Algorithm Sensor in the Research of College Student Security Management System. (7th July 2022) - Wu, Kexu; Li, Chaolin
Abstract : In order to solve the problem of information leakage in the process of college students' information security management, this paper proposes a design of college students' security management system based on a symmetric encryption algorithm. The system is based on the principle of the symmetric encryption algorithm and follows the principle of encryption independence to ensure the security and reliability of the system. The general framework of the system is analyzed in detail. Secondly, the security and database of system function modules are designed, and finally, the performance of the system is tested. The results are as follows: the safety management system designed in this paper has obtained satisfactory evaluation in the trial universities, accounting for 93% of the trial population. It is proved that this system has clear authority design, high efficiency, and security. Managers can query students' basic information, students' real-time location, alarm data information, and so on in real time, which can ensure students' safety to the greatest extent.